2008
DOI: 10.1002/cm.20321
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of tropomyosin extends cooperative binding of myosin beyond a single regulatory unit

Abstract: Tropomyosin (Tm) is one of the major phosphoproteins comprising the thin filament of muscle. However, the specific role of Tm phosphorylation in modulating the mechanics of actomyosin interaction has not been determined. Here we show that Tm phosphorylation is necessary for longrange cooperative activation of myosin binding. We used a novel optical trapping assay to measure the isometric stall force of an ensemble of myosin molecules moving actin filaments reconstituted with either natively phosphorylated or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 71 publications
2
43
0
Order By: Relevance
“…2). These Hill coefficients are consistent with our previous evidence suggesting that phosphorylated Tm extends cooperative activation beyond one thin filament regulatory unit (11).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…2). These Hill coefficients are consistent with our previous evidence suggesting that phosphorylated Tm extends cooperative activation beyond one thin filament regulatory unit (11).…”
Section: Resultssupporting
confidence: 92%
“…In the ␣ isoform of Tm found in striated muscle, there is a phosphorylation site near the carboxyl terminus at Ser-283 (10). This phosphorylation site is in the head-to-tail overlap between neighboring Tm dimers, and we showed previously that Tm phosphorylation is necessary to extend cooperative activation beyond one regulatory unit (11). We also found that actin filaments decorated with phosphorylated Tm (AϩTm.P) produced greater isometric force at intermediate densities of myosin than bare actin filaments or actin filaments decorated with dephosphorylated Tm (AϩTm.DP) (11).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Phosphorylation of Tpm does not cause measurable changes in direct interactions with actin but alters the recruitment of myosins onto thin filaments (Rao et al, 2009). Structural studies indicate that this phosphorylation causes an increase in stiffness of the Tpm-Tpm binding junction (Lehman et al, 2015).…”
Section: Tropomodulins and Tropomyosins – Discovery Structure And Rmentioning
confidence: 99%